Plan de negocio para la implementación de una Boutique de Ropa de Marca en el cantón Piñas, provincia de El Oro, año 2022. - Sagbay Fernandes, Cinthia Lisbeth (2023)
The present research work, aims for the implementation of a brand clothing boutique in Piñas canton through a business plan where the following was examined: marketing plan, production plan, administrative plan and financial plan; through bibliographic information from reliable sources and a structured survey directed towards the supply and demand of the product, obtaining as a sample 373 consumers on the demand side and 114 producers on the supply side. Among the main results: For the first year of opening, the brand clothing market in Piñas canton presents an unsatisfied demand of 42312.17 garments; the installed capacity will cover 5%, that is 2137.5 garments; the investment reaches an amount of 54,090.82 which will be covered by own financing accompanied by a credit granted by the International Bank; the analysis of the break-even point the Boutique Fashions Piñas will obtain its break-even point when it works with an installed capacity of 10.96% and when it sells $ 50. 668.54; the financial evaluation indicates that, the NPV is $294,701.42, IRR 75%, the company will recover its capital in 2 years, 2 months and 26 days since each dollar invested the company earns 59 ctvs. Which determines that it is feasible the implementation of the branded clothing store. Key words: Branded clothing - business plan – Piñas city - boutique – service.